2018
DOI: 10.1113/ep086673
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional morphology and volume of the free Achilles tendon at rest and under load in people with unilateral mid‐portion Achilles tendinopathy

Abstract: Mid-portion Achilles tendinopathy (MAT) adversely affects free Achilles tendon (AT) structure and composition. However, it is not known how these pathological alterations associated with MAT change the normal three-dimensional (3-D) morphology of free AT at rest and under load throughout the entire free tendon length. Here, we used 3-D ultrasound to examine the effect of unilateral MAT on free tendon 3-D morphology [length, cross-sectional area (CSA), anteroposterior (AP) diameter and mediolateral (ML) diamete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 48 publications
2
19
0
Order By: Relevance
“…The resting free tendon's CSA in the present study was on average 31% greater for the tendinopathic compared to the healthy tendons, which is within the 20-66% range reported in other studies (Arya and Kulig, 2010;Nuri et al, 2017bNuri et al, , 2018. The mean free Achilles tendon volume was similarly greater in the tendinopathy group in the present study, although this volume difference relative to the healthy tendons only approached statistical significance (p = 0.07).…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…The resting free tendon's CSA in the present study was on average 31% greater for the tendinopathic compared to the healthy tendons, which is within the 20-66% range reported in other studies (Arya and Kulig, 2010;Nuri et al, 2017bNuri et al, , 2018. The mean free Achilles tendon volume was similarly greater in the tendinopathy group in the present study, although this volume difference relative to the healthy tendons only approached statistical significance (p = 0.07).…”
Section: Discussionsupporting
confidence: 70%
“…Previous studies reported that mid portion Achilles tendinopathy is characterised by tendon thickening (Arya and Kulig, 2010;Nuri et al, 2017bNuri et al, , 2018 and altered material properties (Arya and Kulig, 2010). This study quantified the relative contributions of tendon thickening and decreased material properties on tissue stress under load in tendinopathic compared to healthy Achilles tendons.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…For this study, 61 patients with chronic mid‐portion AT (age: 41.2 ± 10 years) were recruited and divided into two groups: EE programme vibration training (n = 30) and EE programme combined with cryotherapy (n = 31) (Figure ). Participants’ inclusion criteria were as follows: aged between 18 and 65 years, having symptoms for at least 3 months, and having mid‐portion Achilles pain (2–7 cm proximal to insertion) on palpation . Exclusion criteria were a lower limb disease within the last 12 months, previous fracture or surgical intervention, any systemic disease, and past negative experiences with EE vibration and cryotherapy interventions.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the contraction tendon surface is slightly lower in the proximal tendon areas at low intensity. Nuri et al 31 contraction in subjects with AT. Our study showed a CSA increase being positive the difference between contraction and at rest, supporting EE and hypertrophy theories.…”
Section: Cross-sectional Areamentioning
confidence: 98%